1984
DOI: 10.1111/j.1600-0536.1984.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand dermatoses in Tromsø

Abstract: As a parallel project to a coronary risk factor survey in northern Norway, 14,667 men and women aged 18-55 years answered questions concerning the occurrence of allergic hand eczema. 364 men (4.9%) and 961 women (13.2%) had had allergic hand eczema during the previous 12 months. 49 men (0.7%) and 105 women (1.4%) claimed to have had one or more sick leaves because of hand eczema during the preceding 3 years. 114 subjects reported both eczema last year and sick leave during the preceding 3 years, of whom 74 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 3 publications
6
38
1
Order By: Relevance
“…The po int prevalence of self-reported hand dermatoses amo ng the wome n of our study was somewhat hig her (11 %) than that of cl inical hand eczema among Lamrni nta usta 's hospital workers (8 %) ( 19). The one-year prevalence of self-reported hand eczema has varied fro m 5 to 9% among men and 11 to 15% among women in studies based on postal surveys of general populatio ns (26)(27)(28). The correspondi ng figures in the present study (7% for the men and 16% for the women) wer e simi lar to these prevalence figures.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The po int prevalence of self-reported hand dermatoses amo ng the wome n of our study was somewhat hig her (11 %) than that of cl inical hand eczema among Lamrni nta usta 's hospital workers (8 %) ( 19). The one-year prevalence of self-reported hand eczema has varied fro m 5 to 9% among men and 11 to 15% among women in studies based on postal surveys of general populatio ns (26)(27)(28). The correspondi ng figures in the present study (7% for the men and 16% for the women) wer e simi lar to these prevalence figures.…”
Section: Discussionsupporting
confidence: 74%
“…Among fe male farm er s, the risk for hand dermatoses was more than twofold, and for hand derm atoses without other sites of derm atosis the risk was fou rfold that of the men ' s. The risk for hand derm atiti s was higher for wo men und er 35 yea rs of age than for older women. There are also other studies that sho w higher hand ec ze ma prevalen ces for women than men, and also hig her prevalences for young women (20,26,27) . In addition to domestic wor k and other environmenta l ex posures , constit ution al factor s of wome n may be in vol ved .…”
Section: Discussionmentioning
confidence: 99%
“…Women under 35 years old were having 3 times more common hand eczema than men. 12 Irritan contact eczema was most frequent in women while allergic contact eczema was most frequent in men. We also found that hand eczema was more frequent in women in our study.…”
Section: Resultsmentioning
confidence: 99%
“…1,12,20,21 Kavli et al asked to 14.667 person if they had an allergic hand eczema during the previous 12 months and found out 4.9% of men and 13.2% of women had had allergic eczema. Women under 35 years old were having 3 times more common hand eczema than men.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies showed that the 1-year median prevalence of hand eczema in the general population was 9.7% (11.4% among women and 5.4% among men) and that the 1-year weighted average prevalence was 9.1% (10.5% among women and 6.4% among men) (Lantinga et al, 1984;Agrup, 1969;Peltonen, 1979;Menné et al, 1982;Kavli & Forde, 1984;Meding & Swanbeck, 1987;Meding & Jarvholm, 2002;Ortengren, 1999;Meding et al, 2001;Brisman J et al, 1998;Montnemery et al, 2005;Bo et al, 2008;Fowler et al, 2006;Hald et al, 2008;Svedman et al, 2007;Lind et al, 2007).…”
Section: Prevalence Of Hand Eczemamentioning
confidence: 99%